Multi-resolution terrain rendering using summed-area tables. (April 2021) - Li, Shi; Zheng, Chuankun; Wang, Rui; Huo, Yuchi; Zheng, Wenting; Lin, Hai; Bao, Hujun
Highlights: An error-bounded screen space terrain rendering approach. Better terrain shading details with self-occlusion and normal filtering. A new multi-resolution terrain rendering algorithm that utilizes summed-area tables (SATs). Graphical abstract: Abstract: Due to the fundamental weaknesses of level-of-detail (LOD) control and rich details in the Geometry Clipmaps, we propose a multi-resolution terrain rendering algorithm that utilizes summed-area tables (SATs) [1] to facilitate the rendering of terrain with better geometric and shading details. First, our algorithm introduces a novel geometric error bound on the screen-based terrain rendering approach that juggles low rendering throughput and better LOD control. Geometric errors are estimated in real-time from SATs, enabling error-bounded geometry clipmap. Second, we utilize Spherical Gaussian (SG) functions to approximate lighting and bidirectional reflection distribution functions (BRDFs), and efficiently calculate outgoing radiance with self-occlusions of the terrain. SATs are utilized to enable the mipmapping of visibility and normal maps. We demonstrate the improvements of our method with experiments on accuracy and efficiency.